Peasant disputes over land, its division and other issues - Vladimir B. Bezgin (Крестьяноведение)
Review of the book: Gatilov E. V. (2024) Lipetsk District of the Tambov Province in 1917–1927: Land Management and Land Conflicts, Voronezh: Kvarta, 167 p. ISBN 978-5-89609-820-1.